Multiregional 1H-MRSI of the hippocampus, thalamus, and basal ganglia in schizophrenia - Ende, Gabriele; Braus, Dieter F.; Walter, Sigrid; Weber-Fahr, Wolfgang; Henn, Fritz A. (European archives of psychiatry and clinical neuroscience, 2003)
Background: The hippocampus, thalamus and basal ganglia are among the brain regions of major interest in schizophrenia. Aims: The purpose of this study was to corroborate previous findings of reduced N-acetylaspartate in the hippocampal and thalamic regions and to investigate possible metabolite changes in the putamen in schizophrenia. Method: MRSI study of the thalamus, basal ganglia, and hippocampus in 13 schizophrenic patients under stable medication and age-matched healthy controls. Results A decrease of the N-acetylaspartate signal was found in the hippocampal region and the thalamus but not in the putamen of patients compared to controls. No significant group differences in the signals from creatine and phosphocreatine, and choline-containing compounds were found in the hippocampal region and the putamen but the signal from choline-containing compounds was decreased in the thalamus of patients. Conclusion: Metabolic processes in the basal ganglia of schizophrenic patients seem to be opposite the hippocampal and thalamus findings.